QUALITY CONFORMITY ANALYSIS OF FROZEN SONLESS MILKFISH IN XYZ SME USING THE SPC APPROACH - Syam, Israwati; Harianti, Harianti; Awaluddin, Awaluddin (Indonesian Journal of Coastal and Marine Studies, 2026)
Frozen boneless milkfish is an innovative processed fishery product with high economic value, but product quality must be maintained to ensure food safety and competitiveness in the market. This study aims to analyze the suitability of frozen boneless milkfish quality at XYZ SMEs using the Statistical Process Control (SPC) approach. The quality parameters observed include sensory tests (color, aroma, taste, and texture), microbiological tests in the form of Total Plate Count (TLC), and measurements of the core temperature of the fish. The study used two storage methods, namely freezer and cold storage, with three storage periods (7, 14, and 21 days) and each was carried out three times. The results showed that all samples met the sensory quality standard with a value of ≥7, the core temperature of the fish was in the range of ≤–18°C, and the TLC value was still below the maximum limit of SNI, which is ≤5×10⁵ colonies/g. However, the results of the SPC analysis using the X-chart and R-chart control charts showed several points outside the control limits, indicating that the production process was not yet fully statistically stable. This indicates that although product quality generally meets standards, variations in the production process still need to be controlled to maintain quality consistency between batches. Therefore, the implementation of continuous quality control and production process improvements are essential to improve process stability and product quality of frozen boneless milkfish.